Evaluation of the effect of protease inhibitors on the viability of Miamiensis avidus using the WST-1 assay. (June 2020) - Shin, Sang Phil; Sohn, Han Chang; Jin, Chang Nam; Lee, Jehee
Abstract: Miamiensis avidus causes scuticociliatosis in cultured olive flounders ( Paralichthys olivaceus ), leading to economic losses in aquaculture in Korea. Quantitative evaluation of the viability of M. avidus is important to develop an effective vaccine or chemotherapeutic agent against it. We used a colorimetric assay based on the reduction of 2-(4-Iodophenyl)-3-(4-nitrophenyl)-5-(2, 4-disulfophenyl)-2H-tetrazolium (WST-1) to quantify the viability of M. avidus. Using this method, we investigated the effect of protease inhibitors on the viability of M. avidus . The assay showed a clear difference in the optical density (OD) of over 10 4 ciliates, and the metalloprotease inhibitors 1, 10-phenanthroline and ethylenediaminetetraacetic acid (EDTA) reduced the viability of M. avidus by more than 90% when used at concentration of 5 mM and 100 μM, respectively. However, different morphological changes in the parasite were observed when exposed to these two inhibitors. These results indicate that the WST-1 assay is a simple and reliable method to quantify the viability of M. avidus, and metalloproteases are excellent targets for the development of agents and vaccines to control M. avidus infection. Graphical abstract: Unlabelled Image Hghlights: The WST-1 assay was used to quantify the viability of Miamiensis avidus . The effect of protease inhibitors on the M. avidus was investigated using WST-1. The metalloprotease inhibitors reduced markedly the viability of M. avidus. Two metalloproteinases caused different morphological changes of M. avidus .